2014
DOI: 10.1038/ijo.2014.30
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation of leptin and adiponectin promoters in children is reduced by the combined presence of obesity and insulin resistance

Abstract: These observations sustain the hypothesis that epigenetic modifications might underpin the development of obesity and related metabolic disorders. They also validate the use of blood leukocytes and MS-PCR as a reliable and affordable methodology for the identification of epigenetic modifications that could be used as molecular markers to predict and follow up the physiological changes associated with obesity and insulin resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
72
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(78 citation statements)
references
References 37 publications
5
72
0
1
Order By: Relevance
“…It was reported that gestational high-fat diet decreases promoter methylation of leptin in the offspring (Khalyfa et al 2013). In humans, the concentration of circulating leptin is altered by obesity and the promoter methylation of leptin is also altered in obese individuals (Garcia-Cardona et al 2014). Moreover, previous published results suggest that the maternal metabolic status before and during pregnancy can alter placental LEP DNA methylation profile at birth and might contribute to metabolic programming of obesity and related conditions (Lesseur et al 2014b).…”
Section: Epigenetic Regulation Of Leptin and Its Consequences On Fetamentioning
confidence: 96%
“…It was reported that gestational high-fat diet decreases promoter methylation of leptin in the offspring (Khalyfa et al 2013). In humans, the concentration of circulating leptin is altered by obesity and the promoter methylation of leptin is also altered in obese individuals (Garcia-Cardona et al 2014). Moreover, previous published results suggest that the maternal metabolic status before and during pregnancy can alter placental LEP DNA methylation profile at birth and might contribute to metabolic programming of obesity and related conditions (Lesseur et al 2014b).…”
Section: Epigenetic Regulation Of Leptin and Its Consequences On Fetamentioning
confidence: 96%
“…In the adipose tissue of diet induced obese (DIO) mice, the methylated fraction of the leptin promoter was decreased by feeding a high-fat diet at the initial stage; however, it increased after 12 weeks of feeding a high-fat diet compared to control and low-fat diet mice [77]. In peripheral blood samples from human obese adolescents, methylation of the LEP promoter was shown to be negatively associated with BMI [78]. Moreover, obese patients who responded to a low-calorie-diet treatment with a weight loss higher than 5% exhibited lower leptin methylation levels in subcutaneous adipose tissue than those who lost less than 5% of their initial body weight [79].…”
Section: Epigenetic Regulation Of Leptin-related Signalling Pathways:mentioning
confidence: 96%
“…S2 -Garc ıa-Cardona) in leucocytes were associated with higher BMI and higher insulin resistance in adolescents. 39 However, whether the epigenetic modulation of LEP genomic region induced by exposure to maternal hyperglycemia is truly maintained later in life will need to be tested in longitudinal studies. The putative long-term effect of LEP epigenetic modulation on child health could be due to programming of adipocytes (i.e., maintaining a relatively lower DNAm levels throughout life) or to modulation of circulating perinatal leptin levels at a critical period of hypothalamic development.…”
Section: Discussionmentioning
confidence: 99%